Isolamento de Streptococcus agalactiae em diferentes órgãos de tilápias do nilo (Oreochromis niloticus) criadas em tanques-rede - Marcusso, Paulo Fernandes [UNESP] (2015)
Streptococcosis is one of the major causes of mortality in tilapia's creation in Brazil, inducing great economic losses. As soon, the study objectived to determinate the frequency of isolation and identification the Streptococcus agalactiae in organs different of Oreochromis niloticus naturally infected, derived from eight fish farms in the northern region of the state of Parana, that presented clinical signs characteristics of streptococcal disease. However, blood samples and fragments (kidney, liver, spleen, heart and brain) were collected. These all samples were plated on solid medium of brain and heart infusion (BHI) added 5% ovine blood and incubated at 29 degrees C for 7 days in aerophilic conditions. Behind, the bacterial growth and from the macro and microscopic features, colonies compatibles with Streptococcus sp. gender, were selected. The species were identified by PCR reaction and confirmed by sequencing of 16S rDNA gene. The results exhibited that in tilapia of Nile infected with S. agalactiae the isolation is more common in brain, kidney and liver in descending order.